Fruit selection by Andean forest birds: influence of fruit functional traits and their temporal variation - Blendinger, Pedro Gerardo (2016)
Fruit selection, i.e., the consumption of fruits disproportionately to their availability, results from the interaction between diet preferences and ecological factors that modify them. We assessed the importance of functional fruit traits to explain fruit selection by birds in Andean subtropical forests, taking into account temporal variation in trait distribution in the assembly of available fruits. During 2 yr, we measured the abundance of ripe fruits and their consumption by birds in a 6-ha plot during 11 bimonthly samplings, and we used 17 phenological, morphological, and nutritional traits to characterize fruits selected by four bird species. Fruit selection was pervasive year-round, highly variable over time and across bird species. Fruit species were selected over time periods shorter than their ripening phenology, and the selection of fruits with particular traits was specific to the fruit-eating species. Maximization in pulp reward per consumed fruit seems to be the main driving force behind fruit selection, indicating that birds select fruits with traits that directly affect net energy gain. Our results can be interpreted in a framework of a hierarchy of foraging decisions, under which the spatiotemporal context of the fruiting environment modifies the relative intake rates of a particular fruit, while the ability to discriminate fruit contents becomes increasingly important on a smaller dimension. We show that fruit-selection properties are contingent on specific fruit traits and particular spatiotemporal conditions, which modify the structure of mutualistic interactions.